Racism : from slavery to advanced capitalism - Wilson, Carter A. (Sage series on race and ethnic relations, 1996)
This volume in the Sage Series on Race and Ethnic Relations seeks to explain the phenomenon of racism throughout history by drawing on and integrating the massive literature on racism coming out of the economic, political, and cultural realms. In so doing, author Carter A. Wilson tackles four major goals: first, to help resolve the major debates surrounding racism; second, to demystify racism; third, to provide an understanding of how racism has been sustained in various historical eras; and finally, to discuss how racism takes on different forms in various stages of history.